Protein networks of voltage-gated Ca2+ channels – proteomic & functional analysis of local Ca2+ signalling - Fakler, Bernd (Henry Stewart Talks, 2013)
Significance and molecular organization of local Ca2+ signalling, Proteomic analysis of the nano-environment of voltage-gated Ca2+ (Cav) channels, Structure and operation of the Cav2 channels from mammalian brain, Operation of Cav-BK channel complexes, Cav-BK complex as a prototypic Ca2+ nano-domain